Overcoming language barriers in paramedic care: a study protocol of the interventional trial 'DICTUM rescue' evaluating an app designed to improve communication between paramedics and foreign-language patients - Eva Maria Noack; Evelyn Kleinert; Frank Müller (BMC, 2020)
Abstract Background It is essential for medical treatment that patients and medical staff can communicate about acute complaints, pre-existing conditions, and the treatment procedure. Misunderstandings can have far-reaching consequences, particularly in time-critical emergencies, which require rapid assessments and decision-making and in which interpreters are rarely available. In this study, we aim to develop a digital communication tool that is to help paramedics communicate with patients who speak hardly any or no German, to monitor its implementation, and to investigate its effect on communication between foreign-language patients and staff. Furthermore, a large amount of data on patients that are cared for in emergency medical services in Germany are collected for the first time. Methods To consider the complex situations of paramedic care and to meet paramedics' demands, we use an action-oriented research approach to develop the tool. We include the staff of the participating emergency medical service stations and software designers in our approach. The tool is then used and evaluated within an open interventional, non-randomised study with two control groups. Control group 1 (German-speaking patients) and control group 2 (non-German-speaking patients treated without the tool) are recruited starting from the first study phase. In the second study phase, an intervention group is additionally recruited, i.e. non-German-speaking patients with whom the tool is used. The primary outcome of the clinical trial is improved communication with non-German-speaking patients in emergencies by means of the communication tool. The secondary outcome is an improved quality and quantity of the collected information. We exploratively observe on-scene times, demands for emergency physicians, and the usage of the intervention. By recording patients' clinical parameters, we consider the severity of the health restrictions. Discussion Our study is an innovative research project in paramedic healthcare comprising the development of a digital communication tool to overcome language barriers in emergency medical services and investigating its usability, acceptance, and effect on communication, in short, its usefulness and value for paramedic care. Additonally, we expect to gain comprehensive information on rescue operations. Trial registration German Clinical Trials Register, DRKS00016719 , registered 08 February 2019, World Health Organization Trial Registration Data Set, http://apps.who.int/trialsearch/Trial2.aspx?TrialID=DRKS00016719